Productivity Efficiency of Main Actors and KP Sector Business Actors Through the Minapadi Smart Fisheries Village Program - Muhammad Yusuf (Indonesian Journal of Economic & Management Sciences, 2023)
Minapadi is one way to optimize the potential of irrigated rice fields and increase farmers' income is to plan land with appropriate technology which is then contained in the Smart Fisheries Village program and implemented by BRPBAP3 to streamline the productivity of Main Actors and KP Sector Business Actors. The results obtained from Minapadi Cultivation business activities include rice harvest. harvesting the Budikdamber catfish, harvesting corn on the bund land. Chili harvest (cycle 1) on bund land and tilapia harvest on 600 m2 caren land: planned for the second week of January 2023